2008
DOI: 10.1136/ip.2008.018341
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of traffic enforcement: case study from Uganda

Abstract: Background:In October 2004, the Ugandan Police department deployed enhanced traffic safety patrols on the four major roads to the capital Kampala.Objective:To assess the costs and potential effectiveness of increasing traffic enforcement in Uganda.Methods:Record review and key informant interviews were conducted at 10 police stations along the highways that were patrolled. Monthly data on traffic citations and casualties were reviewed for January 2001 to December 2005; time series (ARIMA) regression was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 16 publications
1
48
1
Order By: Relevance
“…All studies except Ditsuwan et al (2013) did not state the discount rate, or conduct sensitivity analyses. Three out of five studies had a time horizon of one year (Bishai and Hyder 2006;Ditsuwan et al 2013;Stevenson et al 2008), one study had time horizon of 10 years (Chisholm et al 2012), and one was unreported (Bishai et al 2008). All future costs and consequences (DALYs and/or life year saved) were discounted to present values at an annual rate of 3% by the studies that reported discounting in their studies (Bishai and Hyder 2006;Bishai et al 2008;Chisholm et al 2012;Ditsuwan et al 2013).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies except Ditsuwan et al (2013) did not state the discount rate, or conduct sensitivity analyses. Three out of five studies had a time horizon of one year (Bishai and Hyder 2006;Ditsuwan et al 2013;Stevenson et al 2008), one study had time horizon of 10 years (Chisholm et al 2012), and one was unreported (Bishai et al 2008). All future costs and consequences (DALYs and/or life year saved) were discounted to present values at an annual rate of 3% by the studies that reported discounting in their studies (Bishai and Hyder 2006;Bishai et al 2008;Chisholm et al 2012;Ditsuwan et al 2013).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…All studies expressed the CEA of intervention in the form of a cost per DALYs averted except Bishai et al (2008) who measured cost per life-year saved. Of five studies, three were undertaken from a societal perspective (Bishai and Hyder 2006;Chisholm et al 2012;Stevenson et al 2008) and one study each from the police department (Bishai et al 2008) and health sector perspective (Ditsuwan et al 2013). All studies except Ditsuwan et al (2013) did not state the discount rate, or conduct sensitivity analyses.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations